Role of Cystic Fibrosis Bronchial Epithelium in Neutrophil Chemotaxis - Cabrini, Giulio; Rimessi, Alessandro; Borgatti, Monica; Lampronti, Ilaria; Finotti, Alessia; Pinton, Paolo; Gambari, Roberto (Frontiers in Immunology, 2020)
Hallmark of the cystic fibrosis (CF) chronic respiratory disease is an extensive neutrophil infiltrate in the mucosa filling the bronchial lumen, starting early in life of CF infants. The genetic defect of the CF Transmembrane conductance Regulator (CFTR) ion channel promotes dehydration of the airway surface liquid, alters mucus properties and decreases mucociliary clearance, favoring the onset of recurrent and, ultimately, chronic bacterial infection. Neutrophil infiltrates are unable to clear bacterial infection and, as an adverse effect, contribute to mucosal tissue damage by releasing proteases and reactive oxygen species. Moreover, the rapid cellular turnover of lumenal neutrophils releases nucleic acids that further alter the mucus viscosity. A prominent role in the recruitment of neutrophil in bronchial mucosa is played by CF bronchial epithelial cells carrying the defective CFTR protein and exposed to whole bacteria and bacterial products, making pharmacological approaches to regulate the exaggerated neutrophil chemotaxis in CF a relevant therapeutic target. Here we revise a) the major receptors, kinases and transcription factors leading to the expression and release of neutrophil chemokines in bronchial epithelial cells; b) the role of intracellular calcium homeostasis and in particular, the calcium crosstalk between endoplasmic reticulum and mitochondria; c) the epigenetic regulation of the key chemokines; d) the role of mutant CFTR protein as a co-regulator of chemokines together with the host-pathogen interactions; e) different pharmacological strategies to regulate the expression of chemokines in CF bronchial epithelial cells by novel drug discovery and drug repurposing.